OUTSOURCING IN DESIGN-PROCESS – PROBLEMS AND OPPORTUNITIES - Ivanova, Diana; Vodenova, Pavlina (Innovation in Woodworking Industry and Engineering design, 2019)
This report reveals the essence of outsourcing as a modern business model. Depending on the field in which it is applied, outsourcing can be considered as production outsourcing and outsourcing of business processes and services. The present study is focused on the outsourcing of business processes and services. The subject of the study is the outsourcing of the design process by business organizations, through which they improve their quality, transfer risk and save money. The purpose of the report is to identify the advantages and disadvantages, problems and opportunities of using outsourcing as a business model. We consider that the research on outsourcing of design process, based on the theoretical formulations and the best practices in this area, will be of interest for researchers and practitioners.